Dr. Munique Maia — Deep Plane Facelift — Washington DC - Maia, Munique (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Munique Maia, practicing in Washington DC, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003152; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; washington dc